Utilizing TPGS for Optimizing Quercetin Nanoemulsion for Colon Cancer Cells Inhibition - Hadel A. Abo Enin; Ahad Fahd Alquthami; Ahad Mohammed Alwagdani; Lujain Mahmoud Yousef; Majd Safar Albuqami; Miad Abdulaziz Alharthi; Hashem O. Alsaab (Colloids and Interfaces, 2022)
Background: Colorectal cancer is one of the most challenging cancers to treat. Exploring novel therapeutic strategies is necessary to overcome drug resistance and improve patient outcomes. Quercetin (QR) is a polyphenolic lipophilic compound that was chosen due to its colorectal anticancer activity. Nanoparticles could improve cancer therapy via tumor targeting by utilizing D-tocopheryl polyethylene glycol succinate (vitamin-E TPGS) as a surfactant in a nanoemulsion preparation, which is considered an efficient drug delivery system for enhancing lipophilic antineoplastic agents. Thus, this study aims to develop and optimize QR-loaded nanoemulsions (NE) using TPGS as a surfactant to enhance the QR antitumor activity. Method: The NE was prepared using a self-assembly technique using the chosen oils according to QR maximum solubility and TPGS as a surfactant. The prepared QR-NE was evaluated according to its particle morphology and pH. QR entrapment efficiency and QR in vitro drug release rate were determined from the selected QR-NE then we measured the QR-NE stability. The anticancer activity of the best-selected formula was studied on HT-29 and HCT-116 cell lines. Results: Oleic acid was chosen to prepare QR-NE as it has the best QR solubility. The prepared NE, which had particles size < 200 nm, maximum entrapment efficiency > 80%, and pH 3.688 + 0.102 was selected as the optimal formula. It was a physically stable formula. The prepared QR-NE enhanced the QR release rate (84.52 ± 0.71%) compared to the free drug. QR-NPs significantly improved the cellular killing efficiency in HCT-116 and HT-29 colon cancer cell lines (lower IC50, two folds more than free drug). Conclusion: The prepared QR-NE could be a promising stable formula for improving QR release rate and anticancer activity.